David Lowenthal, The Heritage Crusade and the Spoils of History, Cambridge University Press 1998 / Roy Rozenzweig, David Thelen, The Presence of the Past. Popular Uses of History in American Life, Νέα Υόρκη, Columbia University Press 1998 - ΓΑΖΗ ΕΦΗ; ΛΑΜΠΡΟΠΟΥΛΟΥ ΔΗΜΗΤΡΑ (Μνήμων, 2002)
Δεν παρατίθεται περίληψη.